Gondolatok a területi kohézióról a Kárpát-medencében a régiótörténeti kutatások szemszögéből - Baranyai, Béla (Közép-Európai Közlemények, 2016)
The paper written from the aspect of regional history – a particle discipline of regional science – starts form the fact that the radical geopolitical rearrangement following World War I resulted in new nation state frameworks in the Carpathian Basin which became the major obstacles for a long time to any cross-border cooperation and the deepening of the neighbourhood relations. For the development of the European regions, favourable conditions have been recently created by those processes strengthening cohesion policy whose longterm result could be the modern re-organisation of integrations that existed for centuries, the birth of a transnational economic space in the Carpathian Basin. Its is a vested interest of Hungary then that the Carpathian Basin, following the similar long-term spatial strategy concepts of the EU, should make a new transnational macro-region in which the Hungarian inhabited areas could be parts of a common space of economic strategy. Leading this initiative, coming from its special geopolitical situation Hungary could also use this as an opportunity, by the system of meaningful cooperations, for the mutually beneficial handling of the dilemmas and disadvantages caused by the Trianon peace treaty.